Interpersonal Values Included in Arabic Language Books of Learning Basic Stage in Jordan - Almashni, Hadil Faisal; Abu Sneina, Odeh Abdel- Gawad (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the values ​​of dealing with the other included in the Arabic language books for the basic education stage in Jordan, and to achieve this, the descriptive analytical approach was adopted. The study sample included Arabic language books for the fourth, fifth and sixth grades in Jordan for the year 2020- 2021, in its first and second parts. A list of the values ​​of dealing with the other that should be included in the Arabic language books was adopted, and its number reached (15) values, after verifying the validity of the tool's content, and the stability of the analysis according to Holstey's equation, where the reliability coefficient for this tool was (0.97%).The study recommended conducting research and scientific studies that are concerned with analyzing the content of textbooks to find out the extent to which they include the values ​​of dealing with others, and more interest in including the values ​​contained in Arabic language books at low rates, and presenting them in a comprehensive and balanced manner.قِيَمُ التَّعَامُلِ مَع الآخَرِ المُتضمّنةِ فِي كُتُبِ اللُّغَةِ العَرَبِيَّةِ لِمَرْحَلَةِ التَّعْلِيمِ الأَسَاسِيّ فِي الأُرْدُنِّ: قيم التعامل مع الآخر، كتب اللغة العربية، مرحلة التعليم الأساسي.Interpersonal Values Included in Arabic Language Books of Learning Basic Stage in JordanHadil Faisal AlmashniOdeh Abdel- Gawad Abu SneinaFaculty of Educational and Psychological Sciences || Amman Arab University || JordanThis study aimed to reveal the values ​​of dealing with the other included in the Arabic language books for the basic education stage in Jordan, and to achieve this, the descriptive analytical approach was adopted. The study sample included Arabic language books for the fourth, fifth and sixth grades in Jordan for the year 2020- 2021, in its first and second parts. A list of the values ​​of dealing with the other that should be included in the Arabic language books was adopted, and its number reached (15) values, after verifying the validity of the tool's content, and the stability of the analysis according to Holstey's equation, where the reliability coefficient for this tool was (0.97%).The study recommended conducting research and scientific studies that are concerned with analyzing the content of textbooks to find out the extent to which they include the values ​​of dealing with others, and more interest in including the values ​​contained in Arabic language books at low rates, and presenting them in a comprehensive and balanced manner.
Keywords: values of dealing with others; Arabic language books; basic education stage